A laminin-receptor-like protein regulates white spot syndrome virus infection by binding to the viral envelope protein VP28 in red claw crayfish Cherax quadricarinatus. (February 2018) - Liu, Ling-ke; Li, Wei-dong; Gao, Yan; Chen, Rong-yuan; Xie, Xiao-lu; Hong, Heng; Wang, Ke-jian; Liu, Hai-peng
Abstract: White spot syndrome virus (WSSV) is a lethal pathogen of shrimp and many other crustaceans, which has been causing huge economic losses in global aquaculture. Laminin receptor (LR) is a cell surface receptor which participates in the interactions between cells as well as cells and extracellular matrix. Previously, we found that a CqLR-like gene was responsive to WSSV infection in the hematopoietic tissue (Hpt) cells from red claw crayfish Cherax quadricarinatus . To further reveal the role of CqLR-like gene involved in WSSV infection, the full-length cDNA of CqLR-like gene was cloned with 1000 bp, and the open reading frame encoded 308 amino acids with a conserved laminin-binding domain. Importantly, both the WSSV entry and viral replication were strongly reduced in Hpt cells after loss-of-function of CqLR-like gene by gene silencing. Protein interaction assay demonstrated that the recombinant CqLR-like protein could bind to WSSV virion in vitro by enzyme-linked immunosorbent assay and the binding affinity was in a dose-dependent manner. Furthermore, recombinant CqLR-like protein was found to bind to WSSV envelop protein VP28, but not other envelop proteins tested including VP19, VP24, and VP26, by pull down assay in HEK293T cells. In regarding to that LR is mainly localized on many types of cells' membrane, these data together suggested that CqLR-like protein was likely to function as a putative recognition molecule towards WSSV and act in the viral entry into a crustacean host cell, which may benefit the elucidation of the WSSV pathogenesis and further the pharmaceutical target for the possibly effective control of WSSV disease. Highlights: CqLR-like gene was expressed widely in various tissues with highest expression in muscle but lowest in epithelial tissue. Loss-of-function of CqLR-like gene clearly inhibited both the WSSV entry and viral replication in the crayfish Hpt cell. CqLR-like protein could recognize the WSSV by binding to the viral envelope protein VP28.